A Multispecies Competitive Nanobody-Based ELISA for the Detection of Antibodies Against Hepatitis E Virus - Arce, Lorena Paola (2023)
The hepatitis E virus (HEV) is an emergent zoonotic virus causing viral hepatitis worldwide. Clinically, hepatitis E is not easily distinguished from other types of acute viral hepatitis. There is a need for HEV diagnostic assays to detect and prevent interspecies transmission among susceptible populations. Nanobodies (Nbs) are expressed recombinantly in different systems, produced with high yields, and have superior physicochemical properties compared with conventional antibodies (Ab). Several Nbs against ORF2, the capsid protein and main antigen, were selected and produced in E. coli. Nb39 and Nb74 specifically recognized HEV ORF2 (genotypes 3 and 4). A competitive ELISA (cELISA) was developed and validated using a reference panel of human (n = 86) and swine sera (n = 116) tested in comparison with a commercial kit. The optimal cutoff values determined by ROC analysis were 69.16% (human) and 58.76% (swine); the sensitivity and specificity were high: 97.4% (IC95%; 86.5–99.5%) and 95.8% (IC95%; 86.0-98.8%) for human vs. 100% (IC95%: 93.5–100%) and 98.3% (IC95%: 91.0-99.7%) for swine. Further, the cELISA detected total anti-HEV antibodies in wild boar, deer, and mice. To our knowledge, this is the first report of production of Nbs against HEV-3 ORF2 for diagnostic purposes.